(3QSGdI GdJLhjOs - (3GdUbQj, GdeWjQaj, GdGMSGFj, GdHMQGfj, YeGO GdOjf, CMeO Hf Rjf GdOjf Hf EHQGgje Hf UbQ, J (B1241(3g`s ((3eMeO bdj Hf ejQRG GdNhFjfjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj fRd GdbQBf JfRjdG(B... (3CeG HYO ajbhd GdYHO GdeScjf CMeO Hf Rjf GdOjf GdCMSGFjs
(3BNQgG (B:s
(3QHfG dGJDBNPfG Ef fSjfG Ch CNWCfG hdG JYGedfG HCYeGdfG hGZaQ dfG(B... (3Efc Ydi cd TjA bOjQ(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B1(3, U(B129s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B185s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs